2002
DOI: 10.1001/jama.287.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness and Sudden-Onset Sleep in Parkinson Disease

Abstract: Excessive daytime sleepiness is common even in patients with PD who are independent and do not have dementia. Sudden-onset sleep without warning is infrequent. The Epworth score has adequate sensitivity for predicting prior episodes of falling asleep while driving and its specificity can be increased by use of the Inappropriate Sleep Composite Score. It is unknown if routinely performing these assessments could be more effective in predicting future risk for these rare sleep attacks. Patients should be warned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
358
6
19

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 537 publications
(401 citation statements)
references
References 26 publications
18
358
6
19
Order By: Relevance
“…In a study of 638 Canadian patients with PD with H&Y stage of 2.2 ± 0.68, Hobson et al. (2002) reported that 51% had EDS; however, in our study, only 26.3% of patients with a similar H&Y stage had EDS. In our patient cohort and that investigated in Switzerland by Poryazova et al., the mean age (65.7 ± 8.88 vs. 65 ± 10 years) and disease duration (8.2 ± 5.2 vs. 8.2 ± 6.6 years) were similar; however, 57% of the patients studied by Poryazova et al.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In a study of 638 Canadian patients with PD with H&Y stage of 2.2 ± 0.68, Hobson et al. (2002) reported that 51% had EDS; however, in our study, only 26.3% of patients with a similar H&Y stage had EDS. In our patient cohort and that investigated in Switzerland by Poryazova et al., the mean age (65.7 ± 8.88 vs. 65 ± 10 years) and disease duration (8.2 ± 5.2 vs. 8.2 ± 6.6 years) were similar; however, 57% of the patients studied by Poryazova et al.…”
Section: Discussioncontrasting
confidence: 75%
“…The occurrence of EDS among patients with PD was lower in Asian than in Caucasian populations in the literature. Studies from Asia using the ESS have reported that the prevalence of EDS ranged from 15.1% to 32.3%; however, prevalence ranging from 40.6% to 57% was reported for Europe and North America (Brodsky et al., 2003; Chen et al., 2015; Goldman et al., 2013; Hobson et al., 2002; Louter et al., 2012; Poryazova et al., 2010; Ratti et al., 2015; Setthawatcharawanich et al., 2014; Tan et al., 2002; Yu et al., 2015; Zhu et al., 2016) (Table 3). Disease severity, disease duration, dopaminergic therapy, and hypnotic medication have been suggested to contribute to EDS; however, neither of them could fully explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the following regimens was used by one motor fluctuator control: venlafaxine (225 mg/day) and trazodone (50 mg/day); paroxetine (20 mg/day) and imipramine (50 mg/day); sertraline 100 mg/day; trazodone (175 mg/day); amitriptyline (50 mg/day). d Equivalent dose of levodopa or dopamine agonists using the method of Hobson et al (2002). Other medications included amantadine (one mood, three motor), selegiline (zero mood, two motor), and benztropine (zero mood, one motor).…”
Section: Discussionmentioning
confidence: 99%
“…route (the intermediatedose protocol in Black et al, 2003). By way of comparison, the average usual morning dose of antiparkinsonian medication in these patients was equivalent to about 250 mg levodopa using the formula of Hobson et al (2002), with no group difference (t-test, p40.30). Seven subjects in each group received levodopa i.v.…”
Section: Protocolmentioning
confidence: 98%